Menyoal Hukum Merokok dalam Perspektif Hukum Islam - Mukri, Muh. (Fakultas Syariah IAIN Purwokerto, 2010)
Ciggarette industry in Indonesia has given much benefit to the country. Even our tobacco is classified as one the best tobacco in the world. However, from Islamic point of view it still becomes controverse. The benefit and the disadvantage of smoking, banning of smoking and analysis from MUI about smoking are discussed n this paper.